2022
DOI: 10.7759/cureus.28881
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Intrawound Vancomycin Powder in Minimally Invasive Spine Stabilization May Cause an Acute Inflammatory Response

Abstract: IntroductionSurgical site infections (SSIs) with methicillin-resistant Staphylococcus aureus are serious complications of spinal instrumentation surgery. Many spine surgeons are concerned that using prophylactic vancomycin powder will lead to certain risks: the development of multidrug-resistant pathogens, anaphylactic reactions, and organ toxicity. Minimally invasive spine stabilization (MISt) is associated with shorter operation times and less blood loss and may therefore require the use of less vancomycin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The proportion of Gram-negative bacilli in the group infected with vancomycin powder was 46.4% in SSIs, whereas the proportion of Gram-negative bacilli in the group infected with non-vancomycin powder was 30.1%. [43] According to the data of this analysis, the dosage of local antibiotics used in most studies was primarily controlled within the range of 1 to 2g. In cases where the skin incision exceeded 20cm, 2g of antibiotics were administered to prevent infection in the wound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of Gram-negative bacilli in the group infected with vancomycin powder was 46.4% in SSIs, whereas the proportion of Gram-negative bacilli in the group infected with non-vancomycin powder was 30.1%. [43] According to the data of this analysis, the dosage of local antibiotics used in most studies was primarily controlled within the range of 1 to 2g. In cases where the skin incision exceeded 20cm, 2g of antibiotics were administered to prevent infection in the wound.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the application of vancomycin powder topically resulted in an acute inflammatory response. [43] Additionally, administering less than 1g of vancomycin powder topically during minimally invasive posterior lumbar disc fusion may decrease the likelihood of SSIs. [44] Further studies are required to ascertain the ideal dosage of antibiotics following spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 trial that included 980 patients with high-risk tibial fractures showed a 3.4% absolute reduction in the risk of deep periprosthetic joint infection with the use of topical vancomycin powder 29 . In the spine literature, comparative studies have supported the benefit of vancomycin powder to reduce the rate of deep infection, although a randomized trial on this topic did not demonstrate a benefit 30,31 and other single-center studies have noted increased C-reactive protein with use of vancomycin powder, as well as a correlation with culture-negative seromas 32,33 . Our findings do not clearly support the use of local antibiotic powder to lower the risk of infection in primary resections, although we noted no evidence of increased antibiotic-related complications with its use.…”
Section: Discussionmentioning
confidence: 99%